Forests for Justice: What is the Sharing of Forest Products between the Government and the Community? - Aris Rudiharto (Universitas Negeri Semarang, 2019)
This research aims to analyze the process of forest production sharing between Perum Perhutani (state-owned forestry company) and LMDH Aman Sentosa as well as the obstacles in the process of forest production sharing between Perum Perhutani and LMDH Aman Sentosa. This research is an empirical and jurudical legal study using qualitative research method. The result of this research shows that the process of production sharing etween KPH Pati and LMDH is a continuous process of the fund sharing which comprises the following processes: (a) the process of teak logging, (b) the calculation of trees and wood production, (c) the submission of sharing proposal for the LMDHs by Asper to KKPH, (d) the KPH team calculated and revised the LMDH’s right proportion, (e) KKPH submitted the proposal to the head of the unit, (f) the unit team conducted a collective correction, (g) the process of making the official report of the sharing and the decree on the allocation of sharing distribution to KPH, (h) KPH Pati issued the decree on the allocation and sharing to the LMDH, (i) KPH Pati passed in the sharing fund to the LMDH, and (j) sharing fund distribution to the members, cash board, and village officials. The obstacles faced in the process of production sharing between Perum Perhutani and LMDH Aman Sentosa are (a) complicated regulation in calculating the production sharing; (b) too long term of the production sharing fund delivery, and (c) LMDH’s delay in submitting the report.